51.7k views
0 votes
Which expression is equivalent to 19x − 6x + 2 and why?

15x, because 19x − 6x + 2 = 13x + 2 = 15x
11x, because 19x − 6x + 2 = 19x − 8x = 11x
2 + 13x, because (19x − 6x) + 2 = 13x + 2 = 2 + 13x
2 − 13x, because (19x − 6x) + 2 = −13x + 2 = 2 − 13x

2 Answers

7 votes
2 + 13x, because (19x − 6x) + 2 = 13x + 2 = 2 + 13x
3 votes

Answer: The correct option is

(C)
2+13x because
(19x-6x)+2=13x+2.

Step-by-step explanation: We are given to select the expression that is equivalent to
19x-6x+2 with reason.

To find the equivalent expression, we need to simplify the expression.

The simplification is as follows :


19x-6x+2=(19-6)x+2=13x+2=2+13x.

Thus, the equivalent expression is
2+13x because
(19x-6x)+2=13x+2.

Option (C) is CORRECT.

User Nicolas Schubhan
by
6.5k points